Proportion and trend in the age of cigarette smoking initiation among adolescent smoking experiencers aged 13-15 years in 148 countries/territories - Shuhui Xing; Min Zhao; Costan G. Magnussen; Costan G. Magnussen; Costan G. Magnussen; Bo Xi (Frontiers Media S.A., 2022)
BackgroundLimited studies have assessed the recent proportion and trend in the age of cigarette smoking initiation among adolescent smoking experiencers globally. We aimed to assess the recent global proportion, associated factors and the long-term trend of the initiated age of cigarette smoking among adolescent smoking experiencers.MethodsWe used data from the most recent Global Youth Tobacco Survey on 99,728 adolescent smoking experiencers aged 13-15 years from 144 countries/territories (hereafter "countries") that had conducted at least one survey in 2010-20, to assess the recent proportion of the age of cigarette smoking initiation. Additionally, we used data from 148 countries that had conducted ≥2 surveys between 1999 and 2020, to assess the trend in the average age of cigarette smoking initiation.ResultsAmong 99,728 adolescent smoking experiencers aged 13-15 years, the proportions of initiating cigarette smoking when aged ≤ 9 years, 10-11 years, 12-13 years, and 14-15 years were 22.8% (95%CI 21.3-24.4), 18.8% (17.3-20.2), 36.8% (34.5-39.2), and 21.6% (19.9-23.2), respectively. The average age of cigarette smoking initiation decreased by 0.44 years per 5 calendar-years averagely in 17 (11.5%) of 148 countries, was unchanged in 95 (64.2%) countries, and increased by 0.38 years per 5 calendar-years averagely in 36 (24.3%) countries. Higher income category (reference group: low-income countries; lower-middle-income: OR = 0.44, 95%CI = 0.28-0.70; upper-middle-income: OR = 0.56, 95%CI = 0.38-0.83; high-income: OR = 0.35, 95%CI = 0.22-0.53) and Framework Convention on Tobacco Control ratification (OR = 0.51, 95%CI = 0.42-0.63) were inversely associated with early cigarette smoking initiation.ConclusionsA substantial proportion (~80%) of adolescent smoking experiencers aged 13-15 years initiated cigarette smoking before 13 years, and the average age of cigarette smoking initiation decreased or remained unchanged in nearly three quarters of the countries surveyed. These findings emphasize that national governments around the world need to strengthen intervention strategies and measures aimed at children and adolescents to prevent smoking up-take.